Role of uncertainty for FDI inflow: Panel econometric analysis of selected high-income nations - Mohammad Anamul Haque; Zhang Biqiong; Muhammad Usman Arshad; Nazia Yasmin (Cogent Economics & Finance, 2022)
The purpose of this study is to evaluate the influence of economic policy uncertainty in determining the FDI inflow for 19 economies with higher incomes between 2000 and 2021. Using the panel Ardl approach, the data were examined. The dynamic fixed effect approach was selected for assessing the necessary set of hypotheses based on the significance of the Hausman test. Increasing levels of economic policy uncertainty, exchange rate, and inflation rate discourage foreign investors from investing in the host country, whereas trade openness and real growth rate increase investors' confidence in increasing FDI inflow in the host country. The economic implications of the study include the political stability of the host country and the uniformity of government policies, particularly in favor of international investors. This study contributes to the existing body of knowledge on FDI by examining the long-term and short-term effects of uncertainty for the high-income group. The findings of the study apply to higher-income economies. In the future, comparative time-series analysis may be used to assess studies on an individual or regional basis for other groups as well.
Keywords: C33; D81; E60; O50; P44; 330; Economic Policy Uncertainty; Exchange Rate; FDI Inflow; Growth Rate; Inflation; Trade Openness